(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
What characterizes any phenomenological approach is the attempt to conceptualize in as close connection with the actual experience of the phenomena as possible. Thus, we have to look for the intentionality in the psychosis, the wild and chaotic structuring of meaning as angst. For psychosis basically has to do with angst in a sense that has been explicated by existentialism, psychoanalysis and phenomenology. The seemingly meaningless expressions of intentionality in psychosis are not so very surprising on the background of Merleau-Ponty’s explications of corporeal intentionality. In his close investigations of intentionality in perception, the body, and language Merleau-Ponty laid open a structuring of meaning which, however incoherent it may be, is sociocultural structuring and which we never escape in our own experience and practice. It is possible to apply different kinds of phenomenological understanding and conceptualization in accord with Merleau-Ponty’s philosophical position. We may distinguish between a structural, a generative and a dialectic understanding of human experience and practices. The application of these approaches implies a constructive criticism of traditional phenomenological views of psychosis and points towards a new understanding of intentionality in psychosis.